If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10ab + -6ab = 0 Combine like terms: 10ab + -6ab = 4ab 4ab = 0 Solving 4ab = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '4'. ab = 0 Simplifying ab = 0 The solution to this equation could not be determined.
| 7(-7+4x)=118 | | 7(6+x)=6(x-3) | | -3(2n-3)=4(5-n) | | y-3*13=13 | | 7(C+2)=3C-5+4C+9 | | 5=4k+53 | | z/4=30 | | 2(9x-8)=19x-15 | | 5x-17=3x+10 | | 2x(5-3)-3=5 | | 4(6)+3= | | 3y+12x=-11 | | 1.1x+1.2+-5.4=-10 | | 8k(4-6)-2x=16(3-k) | | 8(2x-3)-4=6x+9x-1 | | 30x-3x=X-2 | | 6x+15-7= | | 2(2n-1)=(n+3) | | 18+8x=9(x-2) | | 2(t-6)+6t=4(2t+3)-10 | | 3(9-3x)=45 | | x-5d=3 | | 6(-4x+5)=246 | | -77=7(1+4b) | | 4+3z-2=9z+9-7z | | 12+4(z-3)=3x+1 | | 5(r+3)-6=3(r-2) | | 3n+9=-3(2n+3) | | -28=7(7n-4) | | X^2=5*x^2-36 | | X+12+5x-17=2x+11 | | 7e^7t=11e^6t |